Some aspects of meat production in pig autochthonous genetic types. I. Data at slaughtering, jointing of carcass and tissue separation - Colatruglio P.; Esposito D.F.; Zullo A.; Fornataro D.; Capone A.; Matassino D. (Tradition and innovation in Mediterranean pig production, 2000)
The research was carried out on 51 pigs, 30 castrated males (CM) and 21 whole females (WF) belonging to Calabrese (n equal to 10 CM and 6 WF), Cinta senese (n equal to 6 CM and 2 WF) and Siciliano (n equal to 14 CM and 13 WF) autochthonous genetic types (AGT). The major results indicated that: (i) no differences exist among AGTs for the refrigerated net dressing percentage, whose value is equal to 89.9 per cent on average; (ii) among the considered cuts, ham from Cinta senese has a greater incidence (27.8 per cent) on refrigerated carcass if compared to Calabrese (26.9 per cent) and Siciliano (27.0 per cent); the same behaviour is observed for neck cut (P less than 0.05); (iii) separable meat from all cuts, except for the ham for seasoning, ranges from 23.5 per cent to 27.5 per cent in Cinta senese and to 27.9 per cent in Siciliano and Calabrese (P less than 0.01).
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)